Awareness Of Nutrition Among School Students Through Media - et. al., Leo Gertrude, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To lead a healthy lifestyle it is important to have sufficient knowledge on nutrition its importance in our daily lives. It is also essential to have this awareness at a younger age so that healthy eating becomes a habit and eventually a lifestyle. To have a clear understanding of what the food we eat contains or the nutrients present in them, it is essential to give nutritional awareness in foods in relation to their performance in the maintaining the body with stamina, help in growth and repair of worn out tissues and also to improve the body’s immunity. This conceptual paper aims to find out the awareness of nutritional knowledge given through media and its effectiveness among students of high school with extensive review of literature.